A photonic circuit for complementary frequency shifting, in-phase quadrature/single sideband modulation and frequency multiplication: analysis and integration feasibility. Issue 14 (6th August 2017) - Hasan, Mehedi; Hu, Jianqi; Nikkhah, Hamdam; Hall, Trevor
Abstract: A novel photonic integrated circuit architecture for implementing orthogonal frequency division multiplexing by means of photonic generation of phase-correlated sub-carriers is proposed. The circuit can also be used for implementing complex modulation, frequency up-conversion of the electrical signal to the optical domain and frequency multiplication. The principles of operation of the circuit are expounded using transmission matrices and the predictions of the analysis are verified by computer simulation using an industry-standard software tool. Non-ideal scenarios that may affect the correct function of the circuit are taken into consideration and quantified. The discussion of integration feasibility is illustrated by a photonic integrated circuit that has been fabricated using 'library' components and which features most of the elements of the proposed circuit architecture. The circuit is found to be practical and may be fabricated in any material platform that offers a linear electro-optic modulator such as organic or ferroelectric thin films hybridized with silicon photonics.